2018
DOI: 10.1007/s11882-018-0818-2
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Insights into the Occupational Mycobiome

Abstract: Purpose of Review The evolution of molecular-based methods over the last two decades has provided new approaches to identify and characterize fungal communities or “mycobiomes” at resolutions previously not possible using traditional hazard identification methods. The recent focus on fungal community assemblages within indoor environments has provided renewed insight into overlooked sources of fungal exposure. In occupational studies, internal transcribed spacer (ITS) region sequencing has recently been utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
(83 reference statements)
3
9
0
Order By: Relevance
“…Previous culture-based studies showed a higher prevalence of Aspergillus and Penicillium [20][21][22]42], which are traditionally the most expected genus in indoors environments. It seems that this is a bias of culture-based procedures as our results are coincident with other molecular approaches [24,43,56]. Nevertheless, Penicillium polonicum and two species of Aspergillus (A. subversicolor and A. flavus) were detected in 50% (6/12) and 33.3% (4/12) of the samples from houses and the genera were also cultured.…”
Section: The Culturable Mycobiomesupporting
confidence: 82%
See 3 more Smart Citations
“…Previous culture-based studies showed a higher prevalence of Aspergillus and Penicillium [20][21][22]42], which are traditionally the most expected genus in indoors environments. It seems that this is a bias of culture-based procedures as our results are coincident with other molecular approaches [24,43,56]. Nevertheless, Penicillium polonicum and two species of Aspergillus (A. subversicolor and A. flavus) were detected in 50% (6/12) and 33.3% (4/12) of the samples from houses and the genera were also cultured.…”
Section: The Culturable Mycobiomesupporting
confidence: 82%
“…Among the filamentous fungi, Aureobasidium was isolated in 70% of the houses, and Penicillium, Aspergillus, Alternaria, and Cladosporium were present in 40% to 60% of the 20 houses and Cladosporium showed the highest number of colonies detected (Supplemental material cultures). All these genera were also the genus Cryptococcus and Malassezia as highly present in indoor environments [23,24,40,43]. The work of Green et al [23] specifically described 41% of the fungal microbiota inside a building as members of Basidiomycota and 55% of Ascomycota species, which is almost the same distribution detected in the houses of our patients.…”
Section: The Culturable Mycobiomesupporting
confidence: 70%
See 2 more Smart Citations
“…Internal transcribed spacer region sequencing revealed fungal taxa commonly detected in occupational environments . Basidiomycota and Agaricomycetes were the most frequently identified fungal sequences in general area samples collected at the Minnesota facility, accounting for 20% of all fungal sequences.…”
Section: Discussionmentioning
confidence: 99%